Seismological structure of the 1.8 Ga Trans‐Hudson Orogen of North America. (24th June 2016) - Gilligan, Amy; Bastow, Ian D.; Darbyshire, Fiona A.
Abstract: Precambrian tectonic processes are debated: what was the nature and scale of orogenic events on the younger, hotter, and more ductile Earth? Northern Hudson Bay records the Paleoproterozoic collision between the Western Churchill and Superior plates—the ∼1.8 Ga Trans‐Hudson Orogeny (THO)—and is an ideal locality to study Precambrian tectonic structure. Integrated field, geochronological, and thermobarometric studies suggest that the THO was comparable to the present‐day Himalayan‐Karakoram‐Tibet Orogen (HKTO). However, detailed understanding of the deep crustal architecture of the THO, and how it compares to that of the evolving HKTO, is lacking. The joint inversion of receiver functions and surface wave data provides new Moho depth estimates and shear velocity models for the crust and uppermost mantle of the THO. Most of the Archean crust is relatively thin (∼39 km) and structurally simple, with a sharp Moho; upper‐crustal wave speed variations are attributed to postformation events. However, the Quebec‐Baffin segment of the THO has a deeper Moho (∼45 km) and a more complex crustal structure. Observations show some similarity to recent models, computed using the same methods, of the HKTO crust. Based on Moho character, present‐day crustal thickness, and metamorphic grade, we support the view that southern Baffin Island experienced thickening during the THO of a similar magnitude and width to present‐day Tibet. Fast seismic velocities at >10 km below southern Baffin Island may be the result of partial eclogitization of the lower crust during the THO, as is currently thought to be happening in Tibet. Key Points: First full crustal seismic models of the Trans‐Hudson Orogen in northernmost Hudson Bay Proterozoic southern Baffin's crust is thicker, and its Moho more diffuse, than neighbouring Archean domains The Vs models for southern Baffin show similarities to the lower crust of Tibet